Surgical and anesthetic management for hepatectomy in two pediatric patients with trisomy 18, pulmonary hypertension, and hepatoblastoma. Issue 6 (25th February 2019) - Lucas, Donald J.; Rubinstein, Jeremy; Gosain, Ankush; Tiao, Greg; Head, Tim; Pratap, J. Nick; Williams, Regan; Helmig, Sara; Geller, James; Langham, Max; Trobaugh‐Lotrario, Angela
Abstract: Children with trisomy 18 are surviving longer and undergoing more aggressive life‐sustaining therapy. This report describes two patients with trisomy 18 and hepatoblastoma (HB) successfully resected in the setting of significant pulmonary hypertension. Forty‐four previously published cases of the association between HB and trisomy 18 are reviewed. With careful multidisciplinary preoperative planning, successful resection of HB in children with trisomy 18 who have significant pulmonary hypertension is feasible. Because HB and trisomy 18 are increasing in prevalence, the need for timely liver tumor resection in the setting of pulmonary hypertension will be more common.